2020
DOI: 10.1136/bmj.m2984
|View full text |Cite
|
Sign up to set email alerts
|

Work related sexual harassment and risk of suicide and suicide attempts: prospective cohort study

Abstract: Objective To analyse the relation between exposure to workplace sexual harassment and suicide, as well as suicide attempts. Design Prospective cohort study. Setting Sweden. Participants 86 451 men and women of working age in paid work across different occupations responded to a self-report questionnaire including exposure to work related sexual harassment between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
(71 reference statements)
1
44
1
2
Order By: Relevance
“…In the linked prospective study, Magnusson Hanson and colleagues convincingly show excess rates of suicide attempts and deaths among people reporting workplace sexual harassment (doi:10.1136/bmj.m2984). 1 These results persist after extensive adjustment, including sex, country of birth, family type, education, income, baseline mental health, and working conditions. Importantly, neither the incidence nor the association with suicidality are limited to women.…”
mentioning
confidence: 99%
“…In the linked prospective study, Magnusson Hanson and colleagues convincingly show excess rates of suicide attempts and deaths among people reporting workplace sexual harassment (doi:10.1136/bmj.m2984). 1 These results persist after extensive adjustment, including sex, country of birth, family type, education, income, baseline mental health, and working conditions. Importantly, neither the incidence nor the association with suicidality are limited to women.…”
mentioning
confidence: 99%
“…Regarding mental health, sexual harassment is linked to suffering depressive symptoms [16][17][18][19][20][21][22][23], anxiety [20] as well as feelings of shame, humiliation and self-blame [17,18]. Furthermore, an association between sexual harassment in the workplace and suicide and suicide attempts has been found [24]. Moreover, other research carried out in different workplace settings has shown that women who suffer sexual harassment develop psychological distress, which refers to a psychological condition that is characterized by negative thoughts and feelings related to anxiety, fear or depression [25] and need later psychotherapeutic or pharmacologic treatment [23].…”
Section: Introductionmentioning
confidence: 99%
“…There has been much research on WSH. Studies have inquired into WSH's antecedents (Ollo-López and Nuñez, 2018; Pina and Gannon, 2012) and consequences (Adams-Clark et al , 2020; Hanson et al , 2020; McLaughlin et al , 2017; Willness et al , 2007), as well as its legal aspects, including policy, enforcement and sanctions (Gomes et al , 2004; McDonald et al , 2010). In addition, a voluminous literature has explored the experiences and perceptions of WSH from the viewpoint of the victims (Bowling and Beehr, 2006), employees (Brunner and Denver, 2014) and observers (Diekmann et al , 2013; Espinoza and Cunningham, 2010; Tseng, 2014).…”
Section: Introductionmentioning
confidence: 99%